1999
DOI: 10.1016/s0736-5748(99)00041-6
|View full text |Cite
|
Sign up to set email alerts
|

Chronic low‐dose maternal exposure to methylmercury enhances epileptogenicity in developing rats

Abstract: Effects of continuous low-dose maternal methylmercury intoxication on the induction and propagation of ictal epileptiform activity induced by 3-aminopyridine, were investigated on the neocortex of 4-weeks-old offspring rats. Epileptogenicity was significantly increased in offspring of mercury-treated animals compared to those of controls, characterized by more frequent occurrence of periodic ictal activity, a facilitated propagation of epileptiform discharges and a strong tendency to generalization. The latenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Crude toxins, like methyl-mercury, can lead to severe epilepsy in both animal (174) and human (175) offspring. Opiates, such as morphine, are frequently abused during pregnancy (176), particularly in high-risk urban populations (177) and prenatal morphine exposure enhances seizure susceptibility in the limbic system of adult male rats (178).…”
Section: Cortex (131) Is Supported By Longitudinal Prospective Studiementioning
confidence: 99%
“…Crude toxins, like methyl-mercury, can lead to severe epilepsy in both animal (174) and human (175) offspring. Opiates, such as morphine, are frequently abused during pregnancy (176), particularly in high-risk urban populations (177) and prenatal morphine exposure enhances seizure susceptibility in the limbic system of adult male rats (178).…”
Section: Cortex (131) Is Supported By Longitudinal Prospective Studiementioning
confidence: 99%
“…For example, rodent and non-human primate models have shown that prenatal exposure to alcohol (e.g., Mooney et al, 2004), hypoxia (De Riu et al, 1995), cocaine (e.g. Lidow, 2003), methylazoxymethanol (Chevassus-au-Louis et al, 1999b), X-irradiation (Algan and Rakic, 1997) and methylmercury (MeHg) (e.g., Kakita et al, 2001) can cause similar structural abnormalities in the cortex; e.g., heterotopias and reduced cortical volume and thickness, in conjunction with decreases in the seizure threshold of offspring (Norman et al, 2009; Chevassus-au-Louis et al, 1999a,b; Oghlakian et al, 2009; Szasz et al, 1999; Russo et al, 2008; De Feo et al, 1995). This finding is consistent with human clinical cases; in addition to genetic mutations (Dixon-Salazar and Gleeson, 2010; Walsh and Engle, 2010), there is a clear correlation between the pathogenesis of epilepsy and exposure to alcohol, methylmercury (MeHg), maternal epileptic seizure (with or without antiepileptic drugs), stroke and infection (Chevassus-au-Louis et al, 1999a).…”
Section: Introductionmentioning
confidence: 99%
“…Electrocorticographic examinations showed a significant increase in the frequency and summated duration of paroxysmal activity and probability of generalized seizures in MeHg-treated animals at both postnatal day 28 (PND28) and PND90; epileptic activity spread over the whole cortical surface of the brains. These data suggest that pre- and postnatal MeHg exposure significantly increased the susceptibility of both young and adult animals to seizures and facilitated propagation of epileptiform activity (Szász et al, 1999, 2002). Similar effects were also seen in the offspring of rats that were exposed to inorganic mercury (Hg 2+ ) under similar experimental conditions, although the effect of Hg 2+ on epileptogenicity appeared to be long-lasting (Szász et al, 2002).…”
Section: Introductionmentioning
confidence: 82%
“…Szász et al (1999, 2002) showed that exposure of rats to low levels of MeHg (0.375 mg/kg body weight/day) during the entire mating, gestation and lactation period significantly enhanced epileptogenicity in their offspring compared with those of age-matched controls in response to chemoconvulsive agent 3- or 4-aminopyridine. Electrocorticographic examinations showed a significant increase in the frequency and summated duration of paroxysmal activity and probability of generalized seizures in MeHg-treated animals at both postnatal day 28 (PND28) and PND90; epileptic activity spread over the whole cortical surface of the brains.…”
Section: Introductionmentioning
confidence: 99%